(untitled) (Gumilyov Journal of Pedagogy, 2026)
The article discusses the importance of developing professional digital competence of future specialists in the implementation of digitalization, which has become one of the priorities of state policy as one of the current issues. Digital competence includes the ability to effectively use information and communication technologies in the educational process, organize interaction with students, and support innovative approaches in solving professional tasks. The professional work of a teacher-psychologist is not limited to delivering educational content, but also includes creating a favorable learning atmosphere in a digital environment, taking into account the peculiarities of the psychological development of students, individualizing the learning process, and using digital diagnostics and consulting tools. The authors note that the digital competence of a teacher-psychologist is a key indicator of professional success, quality of education, and the effectiveness of psychological services. In accordance with the research problem, the article describes theoretical analyses, methodological opportunities, and practical applications, and makes a number of recommendations and conclusions. Effective methods, stages, components, levels, indicators and criteria, models and directions for developing the professional competence of future educational psychologists, as well as issues of their readiness to perform socio-psychological work, are highlighted. The results of the study indicate that the development of digital literacy is one of the main priorities in improving the professional competence of educational psychologists.